(untitled) (Лучшие интеллектуальные исследования, 2024)
Abstract;This article explores the multifaceted ways in which language constructs shared meanings, sustains social norms, and reinforces or challenges power relations. Drawing on theories from thinkers like Michel Foucault and the Sapir-Whorf Hypothesis, it examines how linguistic categories shape worldviews, how language is used to legitimize authority in institutions like law and religion, and how it perpetuates or resists social hierarchies. Additionally, the role of language in fostering collective identities, as seen in nationalism and cultural preservation, is analyzed alongside its capacity for resistance and transformation. The essay concludes by emphasizing the fluidity of language as a reflection of evolving societal values and a tool for fostering more inclusive realities.